Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO299/2 - Morelia Urlaub; Elisa Klein; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV SONNE during cruise SO299/2 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 2023-08-15 – 2023-09-02 from Singapore to Port Louis (Mauritius) in the central Pacific Ocean. The main scientific focus was on Krakatau archipelago in the Sunda Strait between the Indonesian islands of Java and Sumatra. The volcanic complex was the source of at least two major tsunamis in historic times. Reflection seismic profiles, hydroacoustic data, and sediment cores were collected West, South, and East of the archipelago. Data were recorded within the EEZs of Papua New Guinea and Indonesia as well as outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.